2017
DOI: 10.1021/jacs.7b04936
|View full text |Cite
|
Sign up to set email alerts
|

Driving CO2 to a Quasi-Condensed Phase at the Interface between a Nanoparticle Surface and a Metal–Organic Framework at 1 bar and 298 K

Abstract: We demonstrate a molecular-level observation of driving CO molecules into a quasi-condensed phase on the solid surface of metal nanoparticles (NP) under ambient conditions of 1 bar and 298 K. This is achieved via a CO accumulation in the interface between a metal-organic framework (MOF) and a metal NP surface formed by coating NPs with a MOF. Using real-time surface-enhanced Raman scattering spectroscopy, a >18-fold enhancement of surface coverage of CO is observed at the interface. The high surface concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 36 publications
0
71
0
Order By: Relevance
“…The overgrowth of ZIF on metallic nanoparticles using our fabrication protocol generates nanoscopic interfacial cavities at the interface between the catalyst surface and the polycrystalline ZIF coating (fig. S2, F to H) ( 18 ). Collectively, these interfacial cavities and MOF’s intrinsic micropores are essential for accumulating N 2 and other reactant molecules at the catalytic surface for NRR, as affirmed from surface-sensitive SERS detections of chemical species located near/at the bifunctional plasmonic and electrocatalytically active metallic surfaces (fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The overgrowth of ZIF on metallic nanoparticles using our fabrication protocol generates nanoscopic interfacial cavities at the interface between the catalyst surface and the polycrystalline ZIF coating (fig. S2, F to H) ( 18 ). Collectively, these interfacial cavities and MOF’s intrinsic micropores are essential for accumulating N 2 and other reactant molecules at the catalytic surface for NRR, as affirmed from surface-sensitive SERS detections of chemical species located near/at the bifunctional plasmonic and electrocatalytically active metallic surfaces (fig.…”
Section: Resultsmentioning
confidence: 99%
“…3E ). Consequently, N 2 gas reactants infuse the ZIF scaffold selectively and eventually concentrate near the electrocatalyst surface driven by the thermodynamically favorable sorption at the interfacial cavities and ZIF’s micropores ( 18 ). The close proximity of N 2 molecules and ethanol (proton source) to the catalytic surface facilitates both intermolecular and surface interactions, eventually activating the electrochemical heterogeneous reduction of N 2 molecules to ammonia when an external voltage is applied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[45] Lee et al reported that under ambient conditions of 0.987 atm and 298 K, real-time surface-enhanced Raman scattering spectroscopy was used to monitor the changes of CO 2 molecules on the Ag@ZIF-8 substrate. [46] A >18-fold enhancement of CO 2 was observed at the interface. The CO 2 molecules transformed into a bent conformation, changing from the gas phase to the quasi-condensed phase, which meant that the cavity MOFs formed at the solid can form a microhigh pressure environment at the interface of the nanoparticle@MOF substrate (Figure 8A,B).…”
Section: Drive and Monitor Gas Reactionsmentioning
confidence: 91%
“…Reproduced with permission. [46] Copyright 2017, American Chemical Society. C) Schematic diagram of gas-liquid reaction in the interfacial cavity.…”
Section: Bioimagingmentioning
confidence: 99%